Limitation of the Lytic Effect of Bacteriophages on Salmonella and Other Enteric Bacterial Pathogens and Approaches to Overcome - Chuan-Wei Tung; Dita Julianingsih; Anna Phan; Christa Canagarajah; Zabdiel Alvarado-Martínez; Debabrata Biswas (International Journal of Microbiology)
Bacteriophages (phages) have emerged as promising agents for combating bacterial pathogens, including nontyphoidal Salmonella enterica (S. enterica), the most common foodborne pathogen worldwide. The emergence of antimicrobial-resistant (AMR) S. enterica poses a severe healthcare issue. Nowadays, many countries worldwide have banned antibiotics for animal feeds or additives, and various strategies have been developed and gained popularity for their potential to address S. enterica infection. Among these strategies, phage therapy shows more promise because of its ability to specifically target bacterial pathogens without disrupting the beneficial microbiota or animal/human cells. Phages are viruses that rupture host cells through the lysis of phage-encoded endolysin proteins. Nonetheless, phages also face various challenges, including phage resistance, gene transduction, serovar diversity, and the immune response of animal/human organisms, which limit the efficacy of S. enterica. Due to this limitation of phages, endolysin, as a lytic protein for bacterial cells derived from phages, has been demonstrated as another promising solution against various bacterial pathogens, including AMR. This review is aimed at discussing the benefits and limitations of phage therapies and exploring the promising potential of phage-encoded endolysins in controlling S. enterica.